Case Report: Spontaneous lung intercostal hernia series and literature review - Ugolini, Sara; Abdelghafar, Moslem; Vokkri, Eduart; Sharkey, Annabel J.; Fontaine, Eustace; Voltolini, Luca; Morabito, Antonino; Ugolini, Dario; Granato, Felice (Frontiers in Surgery, 2023)
Spontaneous lung intercostal hernia (SLIH) is a rare condition potentially carrying severe morbidity. About 120 cases have been described so far, with an apparently increasing number of reports in recent years. The main presenting findings are chest pain and bulging, with ecchymosis in the affected area, hemoptysis, respiratory distress, and signs of infection or incarceration being described as well. The gold standard treatment has not been established, and conservative management has been advocated as first-line treatment for asymptomatic patients. Here, we report a case series of five patients, and surgical repair was deemed necessary for four of them either at first evaluation or after failure of conservative management. One patient remains under surveillance and conservative management. We believe that SLIH surgical repair should be considered as first-line treatment for fit patients, due to the uncertainty of its mid- and long-term impact and described pejorative trend/defect enlargement. A proposed algorithm for SLIH management is also presented.